El punitivismo penal en el Ecuador planteado como salida a la ola de criminalidad. - Vega Jiménez Olmes David (2024)
Criminal law is a social containment tool through which the State seeks to punish certain behaviors that endanger or damage certain protected legal assets. However, this is the last resort of containment against such behaviors, so that prior to the application of sanctions, other extrapenal mechanisms must be sought. Based on the punitive idea of penal punitivism, another much more recent idea arises, which is penal populism, an idea based on the urgency to curb social chaos through the increase of penalties and the strengthening of containment agencies such as the number of members of the public order forces and the prison infrastructure under a solely punitive purpose, This is very different from the idea sustained by the penal guarantee system, which proposes the limitation of the punitivist power of the state, thus complying with the constitutional and conventional system precipices whose purpose is to prevent abuse by the state authority. This research is justified by the need for an analysis of the social and legal reality of the current problem where the increase of penalties (criminal punitivism) is discussed as a way out of the criminality that Ecuador is going through, without first making a holistic analysis of the root of the problem, on the real issues that give rise to it. This research aims to conduct a study of criminal punitivism as a measure that seeks to address the crime wave in Ecuador and to determine possible alternative or complementary measures to reduce this problem that afflicts Ecuadorian society. The methodology of this research is qualitative and explanatory since it will seek to make a dogmatic-legal analysis of the issue raised. The expected results at the end are: to define punitivism and penal guaranty as well as the causes of criminality in Ecuador and the different mechanisms as a possible solution to the problem raised, whose transfer of these results will be made through the defense of this research. Key words. Punitivism, Populism, Criminality, Punishment, Criminal Law.